Investigation of the emulsions based on functional food compositions containing protein - Пасічний, Василь Миколайович; Страшинський, Ігор Мирославович; Фурсік, Оксана Петрівна (Technology audit and production reserves, 2015)
The increasing deficit of raw meat and its quality reduction necessitates the improvement of existing technologies that would allow not only the rational and efficient usage of raw meat, but also other sources of food proteins. Effective ingredients that can improve the unstable functional- technological properties of raw meat are zoogenic and phytogenic protein substances and hydrocolloids. After analyzing the literary sources rational balance of food additives was chosen to create a functional food compositions. For recipes of created compositions indicators of emulsion sustainability and emulsifying ability were examined, what enabled to determine the ability to create a composition to absorb and store fat in its structure. Taking into account high stability indicators of the emulsion (45-18 %), and emulsifying ability (91-53 %) recipe number 3 is the best. Positive impact of food additive E551 (silica) on these indicators was proved, because the stability of the emulsion and emulsifying ability increased by an average 3-5 %.